Alimentary and technological processing of guanacos (lama guanicoe) during the late holocene: The case of coastal site marazzi 32 (Tierra del Fuego, Chile) Procesamiento alimenticio y tecnológico de guanacos (Lama guanicoe) durante el Holoceno tardío: El caso del sitio costero Marazzi 32 (Tierra del Fuego, Chile) - Sierpe Gonzalez, Victor Manuel; Morello Repetto, Flavia; Massone, Mauricio; Palacios, Cristóbal (My University, 2019)
The analysis of the guanaco assemblage recovered from Marazzi 32 archaeological site, Isla Grande de Tierra del Fuego, is presented. The site, dated between 560 and 635 BP, is noteworthy for its record of cetacean bones, mostly found on the surface, and the prevalence of guanacos in relation to other marine mammals, birds and taxa. Results confirmed the importance of guanaco remains in the subsistence and supply of bone raw material, supporting the economic theory that has traditionally considered that land resources played a fundamental role for human groups during the late Holocene. The significance of guanaco exploitation at the site, the greater number of young individuals, and the exploitation strategies, food chain, and technological management of the species are discussed.
Keywords: bone tools; exploitation; patagonia; terrestrial hunter-gatherers; zooarchaeology